PENGEMBANGAN MEDIA PEMBELAJARAN IPAS BERBANTUAN HEYZINE FLIPBOOK BERBASIS RADEC DI KELAS III SEKOLAH DASAR - Dwi Kurnia, Yesa; Amini, Risda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The 21st century is characterized by openness and globalization, which have brought significant changes in various fields, including education. However, based on preliminary studies conducted in several elementary schools, science and social studies (IPAS) learning still faces challenges, particularly due to the use of conventional learning media and the suboptimal utilization of technology. This condition results in less interactive learning processes and limited student engagement. Therefore, an innovation is needed in the form of developing IPAS learning media assisted by Heyzine Flipbook based on the RADEC (Read, Answer, Discuss, Explain, Create) model, which is expected to enhance students’ activeness and understanding in third-grade elementary school. This study is a Research and Development (R&D) study aimed at producing learning media that are valid, practical, and effective. The development model used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collected in this study include validity, practicality, and effectiveness of the media. The results of the validity test show percentages of 92% from material experts, 97.5% from language experts, and 95% from media experts, with an overall average of 94.8%, categorized as “very valid.” The practicality test results indicate that teachers’ assessments range from 82.5% to 90%, and students’ assessments range from 82.71% to 95.14%, all categorized as “very practical.” Meanwhile, the effectiveness test shows scores ranging from 0.34 to 0.60, categorized as “moderately effective.” In conclusion, the IPAS learning media assisted by Heyzine Flipbook based on the RADEC model is proven to be valid, practical, and moderately effective in supporting the learning process in third-grade elementary school.